2017
DOI: 10.1111/tid.12661
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Acanthamoeba infection in a heart transplant recipient treated successfully with a miltefosine‐containing regimen: Case report and review of the literature

Abstract: Disseminated acanthamoebiasis is a rare, often fatal, infection most commonly affecting immunocompromised patients. We report a case involving sinuses, skin, and bone in a 60-year-old woman five months after a heart transplant. She improved with a combination of flucytosine, fluconazole, miltefosine, and decreased immunosuppression. To our knowledge this is the first case of successfully treated disseminated acanthamoebiasis in a heart transplant recipient and only the second successful use of miltefosine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…and the result of organ transplantation were also reported. 19,20 GAE is a chronic or subacute disease that causes headaches, fever, fatigue, as well as spasms and limb paresis 1 (Table 1). Recent reports indicated a relationship between GAE and cognitive dysfunction (Table 1) similar to cases of encephalomyelitis caused by archaea.…”
Section: Introductionmentioning
confidence: 99%
“…and the result of organ transplantation were also reported. 19,20 GAE is a chronic or subacute disease that causes headaches, fever, fatigue, as well as spasms and limb paresis 1 (Table 1). Recent reports indicated a relationship between GAE and cognitive dysfunction (Table 1) similar to cases of encephalomyelitis caused by archaea.…”
Section: Introductionmentioning
confidence: 99%
“…Literature presents three cases of cardiovascular patients with acanthamoebiasis [6,36,37], although no parasite forms have been found in cardiac muscle cells [37]. Also, in this study no trophozoites or cysts were found in myocardial histological preparations from Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 46%
“…trophozoites enter into the tissue or organs and induce granulomatous amoebic encephalitis (GAE), Acanthamoeba keratitis (AK) or disseminated acanthamoebiasis [3,4]. Disseminated acanthamoebiasis is predominantly con rmed post-mortem by histopathological examination of the organs and/or re-isolation of amoebae from tissue fragments [5] because biochemical and hematological tests are di cult to interpret; blood parameters may be elevated, lower or not deviating from the norm [6]. In our earlier study concerning hematological and biochemical pro les in the blood of experimentally Acanthamoeba spp.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature presents three cases of cardiovascular patients with acanthamoebiasis [ 6 , 36 , 37 ], although no parasite forms have been found in cardiac muscle cells [ 37 ]. Also, in this study no trophozoites or cysts were found in myocardial histological preparations from Acanthamoeba spp.-infected mice, despite the fact that developmental forms of Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…trophozoites enter into the tissue or organs and induce granulomatous amoebic encephalitis (GAE), Acanthamoeba keratitis (AK) or disseminated acanthamoebiasis [ 3 , 4 ]. Disseminated acanthamoebiasis is predominantly confirmed post-mortem by histopathological examination of the organs and/or re-isolation of amoebae from tissue fragments because biochemical and hematological tests are difficult to interpret; blood parameters may be elevated, lower or not deviating from the norm [ 5 , 6 ]. In our earlier study concerning hematological and biochemical profiles in the blood of experimentally Acanthamoeba spp.-infected mice, we found only higher level of lymphocytes, monocytes, thrombocytes and aspartate aminotransferase [ 7 , 8 ], despite the re-isolation of these amoebae from the brain, eyeball, lungs, kidneys, and spleen of the mice [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%